THE INFLUENCE OF GLOBAL TRANSFORMATIONS ON THE SOCIO-ECONOMIC SUPPORT FOR THE DEVELOPMENT OF RURAL AREAS OF UKRAINE IN THE POST-WAR PERIOD - IATSENKO, Oleksandr; YATSENKO, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the impact of global transformations on the socio-economic support for the development of rural areas in Ukraine under wartime challenges and post-war recovery. It is substantiated that the combination of economic, social, environmental, digital, and institutional changes forms a new architecture of spatial development and determines the resilience of rural communities to external shocks. It is shown that the full-scale war has significantly intensified structural problems of rural territories, including declining investment activity, labor outmigration, infrastructure destruction, and reduced employment. The study analyzes the dynamics of key socio-economic indicators of rural development in Ukraine during 2015–2024, which made it possible to identify trends in investment flows, wage levels, and employment in the agricultural sector. Socio-economic support for rural development is interpreted as a comprehensive system that includes economic, social, infrastructural, institutional, and environmental components, the interaction of which creates the basis for an innovation-oriented model of sustainable development. A multi-level model of rural development management in the post-war period is proposed, integrating national, regional, economic, social-educational, and environmental levels. It is argued that the implementation of this model will promote economic diversification, human capital development, digitalization of governance, the introduction of green economy principles, and improvement of the quality of life of the rural population. The study concludes that the adaptation of Ukraine’s rural areas to global transformations is a key prerequisite for their sustainable development and integration into the European space of sustainable growth.